(untitled) (Baghdad Science Journal, 2024)
Due to its availability, affordability, effectiveness, and low cost, the green-based synthesis of silver nanoparticles by plants is gaining popularity. It is safe to handle and has a wide range of metabolites, including antioxidant and antibacterial activities. The production of AgNPs was established in this work utilizing aqueous and methanolic extracts of fresh Camellia sinensis leaves that reduced silver nitrate. This process enabled the creation of NPs, which were then characterized using a range of analytical techniques including ultraviolet-visible (UV-Vis) spectrophotometry, Fourier Transform Infrared spectroscopy (FTIR), Atomic Fluorescence Microscopy (AFM), X-ray scattering (XRD), and Zeta potential analyzer. The color of aqueous silver nitrate changes following treatment with fresh leaf extracts, and was confirmed by UV-Vis spectra. In addition, the AFM analysis that showed particles were spherical, either individually or together with average sizes 108.3 and 84.76 nm for aqueous and methanolic extracts respectively. The crystalline nature of the nanoparticles was verified by the XRD method. The average size was estimated according to the Scherrer equation and they were 61.24, 99.66 nm for Camellia sinensis silver nanoparticles (CANPs) aqueous and methanolic extracts respectively. In addition the zeta potential values were -30.31 and -32.33 mV for CANPs aqueous and methanolic extracts respectively.